Regulatory and Quality Aspects of Bio Absorbable Bandages for Intestinal Wound Healing - Murthannagari, Vivek Reddy; Nagarajan, Jeswanth Raj; Krishnan, Ganesh Gonna Nandi; Ponmurugesan, Karthikesavan; Devaraj, Hemalatha Thavani; Jani, Krushika (International Journal of Pharmaceutical Investigation, 2025)
Surgical intestinal wound healing is a significant cellular process managed by several cellular and molecular factors. The present review aims to focus on the evolution of medical device bandages that can help improve the healing of intestinal injuries in patients who undergo gastrointestinal surgery or suffer from IBD. Restitution, proliferation and differentiation of IECs are critical for wound healing in the gut and restoration of barrier function. For example, patients with diabetes develop poor wound healing and associated consequences such as anastomotic leak or fistula formation. These challenges are discussed in this review to show how smart and bioelectronic bandages can help to overcome these by offering the necessary healing conditions through moisture, monitoring and drug release. For instance, smart bandages covered with sensors and bioelectric bandages open unique therapeutic perspectives due to the stimulation of cell migration and anti-inflammatory action. These innovations are much better than the conventional bandages, for they hold the potential in improving clinical outcome of wounds. Further research should be directed at working on the practicality, affordability and sustained clinical effectiveness of such functional bandages so that they can be incorporated in daily practice.
Keywords: Advanced Therapeutic Bandages; Cyborg Bandages; Gastrointestinal operations; Inflammatory Bowel Disease; Intestinal Wound Healing; Medical Device Therapeutic Bandages and epithelial cell repair